The Relationship between Interior Design and Historical Society (An Analytical Study) - Thabit Al-Baldawi , Mohammed (Dirasat: Human and Social Sciences, 2022)
The interior design is a living and honest expression of the culture of people, it shows the strong and clear relationship of the community in architecture and inte ________________________________________________ * Digital Arts & Design , Khwarizmi University Technical College. Received on 23/1/2020 and Accepted for Publication on 8/2/2021. rior design throughout history since the beginning of creation. This study aims to shed light on the following lines: The relationship of interior design to society, the study of internal design and its historical development, and analysis by using the analytical descriptive approach to residential houses in Amman. The study concluded with a set of recommendations: Highlight developments that accompanied architecture, Dealing with the latest developments of technology in terms of subjecting the thought of the designer and the philosophy of his community by adapting them to this thought, and Dealing with the environment in an overall concept to achieve the concept of sustainability in design and in order to reach the highest quality.